Frontiers in Advanced Materials for Energy Harvesting and Storage in Sustainable Technologies - Sujata Saini; Shabnum Shafi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The global pursuit of sustainable energy has spurred transformative innovations in materials designed for energy harvesting and storage, enabling efficient utilization of renewable resources. This manuscript examines recent progress in energy harvesting technologies, including piezoelectric, thermoelectric, and photovoltaic systems, which convert ambient energy sources like vibrations, heat, and sunlight into electrical power. Simultaneously, advancements in storage solutions, such as solid-state batteries, supercapacitors, and novel electrode materials, enhance energy retention and delivery. The integration of nanostructured composites, two-dimensional materials like graphene, and bio-inspired designs has significantly improved energy conversion efficiency, storage capacity, and cycle stability. These developments address critical challenges, including scalability, cost-effectiveness, and environmental sustainability, through initiatives like battery recycling and the use of non-toxic materials. The abstract explores diverse applications, from wearable electronics and autonomous devices to grid-scale energy storage, and underscores the importance of interdisciplinary research to drive the transition toward a clean energy future.